2011
DOI: 10.5194/acp-11-4767-2011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trimethylamine on atmospheric nucleation involving H<sub>2</sub>SO<sub>4</sub>

Abstract: − 10 7 cm −3 and the slopes of Log J vs. Log [H 2 SO 4 ] and Log J vs. Log [TMA] were 4-6 and 1, respectively, strikingly similar to the case of ammonia (NH 3 ) ternary nucleation (Benson et al., 2011). At lower RH, however, enhancement in J due to TMA was up to an order of magnitude greater than that due to NH 3 . These findings imply that both amines and NH 3 are important nucleation species, but under dry atmospheric conditions, amines may have stronger effects on H 2 SO 4 nucleation than NH 3 . Aerosol mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
171
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 64 publications
9
171
0
Order By: Relevance
“…Water vapor has also been reported to play a role in particle formation from H 2 SO 4 and amines. 22,26,27,66,67 The reaction order of 2 with respect to H 2 O does not imply an elementary reaction involving two water molecules nor the number of water molecules in a critical cluster, but rather the involvement of water in the rate-determining step(s). 68 The second order dependence is captured by the individual steps in the kinetics model as discussed below, and is attributed to the involvement of water in forming the reactive MSA hydrates and/or in subsequent rate-determining step(s).…”
Section: Particle Formation and Growth As A Function Of Precursor Conmentioning
confidence: 99%
See 1 more Smart Citation
“…Water vapor has also been reported to play a role in particle formation from H 2 SO 4 and amines. 22,26,27,66,67 The reaction order of 2 with respect to H 2 O does not imply an elementary reaction involving two water molecules nor the number of water molecules in a critical cluster, but rather the involvement of water in the rate-determining step(s). 68 The second order dependence is captured by the individual steps in the kinetics model as discussed below, and is attributed to the involvement of water in forming the reactive MSA hydrates and/or in subsequent rate-determining step(s).…”
Section: Particle Formation and Growth As A Function Of Precursor Conmentioning
confidence: 99%
“…33,40,41 Results from quantum chemical calculations show that amines are much more strongly bound to H 2 SO 4 than NH 3 , 25 and laboratory experiments have demonstrated higher efficiencies of amines in particle formation compared to NH 3 . 22,[26][27][28] In addition, amines have been shown to displace NH 3 in sulfate particles and clusters. [42][43][44][45] Based on these results, small particles are more likely to be aminium salts even if ammonium salts are initially formed.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Many studies have been performed to explore the enhancement effect of amines in nucleation in competition with ammonia. [31][32][33][34][35][36][37][38][39][40][41][42] In the past two decades, on-line single particle mass spectrometry has made significant contributions to the studies of ambient aerosols. [43] Using this technique, the size and composition of many individual particles can be determined simultaneously with good time resolution, allowing particle composition to be correlated with rapid changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of amines for NPF has recently been established by field (Angelino et al, 2001;Makela et al, 2001;Smith et al, 2010;Zhao et al, 2011) and laboratory experiments (Murphy et al, 2007;Berndt et al, 2010;Erupe et al, 2011;Bzdek et al, 2010;Zhao et al, 2011;Yu et al, 2012;Zollner et al, 2012;Almeida et al, 2013;Jen et al, 2014;Kurten et al, 2014), as well as from modelling studies (Kurten et al, 2008;Barsanti et al, 2009;Bzdek et al, 2010;Ortega et al, 2012;Loukonen et al, 2010;Nadykto et al, 2011;Paasonen et al, 2012;Almeida et al, 2013;DePalma et al, 2014). On a molecular level, Kurten et al (2014) observed how DMA stabilises SA, increasing the stable cluster concentration by up to 6 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%